Training and Mentoring for Elementary Teachers in Making STEM-Based Digital Assessment Instruments - Ermawati Diana; Lovika Ardana Riswari; Esti Wijayanti (Journal of Community Service and Empowerment, 2025)
Digital assessment also known as digital evaluation is the process of collecting, analyzing, and reporting data from research using digital technology or special research tools. DIGASS is a website application that can be accessed anywhere and is used to assess STEM-based students before being tested on students. The method of solving the problem is through training and mentoring in creating STEM-based digital assessment instruments or DIGASS applications. This training was attended by 8 teachers of SD Negeri 1 Pringtulis. The training and mentoring materials include: (1) Introduction to STEM-based digital assessment applications, (2) Various methods that can be used in digital assessment, (3) How to create digital assessment instruments, (4) Testing assessment instruments. This training and mentoring succeeded in increasing the knowledge and skills of SDN 1 Pringtulis teachers in creating STEM-based digital assessment instruments. This training and mentoring succeeded in helping improve the competence and literacy of digital teachers in creating digital assessment instruments through the DIGASS application. So that later teachers can apply digital assessment in classroom learning. Teachers can also train students to be proficient in utilizing technology.